Schoenberg contra Schenker contra Schoenberg: polemics against dissonance, motive and form and their possible reconciliations (Orfeu, 2021)
This text addresses one of the most important polemics of 20th century music theory and analysis. The clash between Schoenberg and Schenker about the legitimacy of non-harmonic notes in tonal music, dissonances, the importance of motive and form. The text seeks to discuss and clarify the concepts on these subjects and their importance for the respective analytical theories of each author. Finally, the text presents the attempts to reconcile the two analytic trends.
Keywords: music theory; music analysis; Schoenberg; Schenker